Scintillation panels based on zinc selenide for detection of alpha radiation - Litichevskyi, V.; Tarasov, V.; Galkin, S.; Lalaiants, O.; Voronkin, E. (Functional Materials, 2012)
The possibility of obtaining dispersed scintillation panels based on zinc selenide for alpha radiation registration has been demonstrated. Thanks to the good energy resolution Rα ~ 30 % of the panel it can be used for the registration of alpha radiation in radiometric and spectrometric modes. In this work the optimal particle size and the effective thickness of the composite layer of powder scintillator have been determined that provides high quantum yield of the panels. Experimental data of the dependence of light output from the panels on the size of the scintillator’s particles at the influence of X-ray and alpha radiation have been presented.